Molecular characterisation of Coxiella burnetii dairy cattle strains in Estonia - Neare, Kädi; Tummeleht, Lea; Jinnerot, Tomas; Lassen, Brian; Viltrop, Arvo (Frontiers in Veterinary Science, 2025)
Coxiella burnetii (C. burnetii), an obligate intracellular zoonotic bacterium, causes abortions, stillbirths, and birth of premature and weak offspring in animals. Sheep and goats, are considered important reservoirs of infection for humans. In Estonia, C. burnetii is detected serologically in domestic ruminants with the prevalence being significantly higher in dairy cattle herds than that in beef cattle herds and sheep flocks. Furthermore, C. burnetii DNA has previously been identified in dairy cattle. This study explored the genetic characteristics of C. burnetii strains to identify possible sources of the disease. The strains found in the Estonian dairy herds were examined using 15-locus multiple-locus variable number tandem repeat analysis (MLVA). Across the two herds, one complete and two partial profiles with different numbers of repeats at the studied loci were identified. A comparative analysis using the unweighted pair group method with arithmetic mean (UPGMA) and randomly selected European profiles detected two larger phylogenetic clusters associated with cattle and small ruminant species, respectively. Additionally, it revealed a relationship of Estonian profiles to C. burnetii profiles detected in abortion material and milk from Belgian cattle. These results provide primary genetic information regarding the Coxiella strains circulating in this region and indicate C. burnetii-induced reproductive disorders in Estonian dairy cattle herds.